Healthy Living Behavior Training as an Effort of Hypertension Problems - Indra Elisabet Lalangpuling; Micahel Valery Tumbol; Allan J. Andaria (Sam Ratulangi University, 2023)
Based on Riskesdas data in 2018, the prevalence of hypertension based on the results of measurements in the population aged 18 years in Minahasa is 24.11%. The proportion of non-adherence to taking the medication regularly is still high. The proportion of routinely measuring blood pressure on a regular basis is still low. The purpose of this community service is to apply technology in the health sector to improve knowledge and skills, form independent community groups in implementing healthy lifestyle patterns in daily life in controlling blood pressure, being obedient and obedient in using drugs that have been prescribed by doctors. This activity was carried out in Kalasey 2 Village, Minahasa Regency. The method in implementing the activity begins with approaching and socializing the activity plan with the government and coordinating with the Tateli Health Center. The types of activities carried out are counseling on